Traumatic diaphragm rupture treated with left anterolateral thoracotomy approach: a case report - Aulia Novariza Fahman; Rama Nusjirwan; Euis Maryani; Navy Laksmono (Journal of Indonesia Vascular Access, 2022)
Background: Traumatic diaphragmatic rupture (TDR) is a life-threatening condition due to the herniation of abdominal organs into pleural cavities. Rupture can occur in patients with major blunt or penetration trauma of the lower chest. Blunt TDR is usually caused by momentary high energy damage and is associated with severe trauma. This study aims to evaluate our hospital's experience with managing patients with blunt TDR, including its incidence, modes of diagnosis, operative treatments, postoperative outcomes, and factors predictive of patient outcomes. Case Report: A 44 years old man was referred to our hospital complaining of dyspnea. Eleven hours before his admission, he was riding his motorcycle, fell to the road, and hit the tree on his left chest. After the accident, he feels dyspnea, chest pain, and abdominal pain. The patient was brought to the nearest hospital and underwent a chest x-ray and left chest tube insertion, with initial production was blood 1700 ml. On examination, there was an increased respiratory rate, a visible bruise of the posteroinferior left chest near the left flank and a pre-installed chest tube thoracostomy on the left chest. Chest x-ray showed an intrathoracic herniation of abdominal viscera, the "collar sign" appeared, and the abdomen x-ray showed the left upper quadrant abdominal organ displaced into the left thorax cavity. Thus suspected, the underlying condition of TDR in this patient. We decided to perform left anterolateral thoracotomy and continued with laparotomy and splenectomy Conclusion: TDR is a rare case. The trauma may include shearing a stretched diaphragm, avulsion from a muscular insertion point, or increased abdominal pressure exceeding the bursting pressure of the diaphragm. Intra-abdominal organ injuries are more common than intrathoracic injuries. Initial operative approaches were laparotomy and thoracotomy.